PENGARUH ARUS KAS DAN LABA AKUNTANSI TERHADAP HARGA SAHAM STUDI EMPIRIS PADA BURSA EFEK INDONESIA - Eka Rina Febriyani; Haryo Kusomo (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
Study aims analyze the effect of accounting profit, cash flow, and stock prices of manufacturing companies listed on the IDX. The sample is companies that have complete cash flow reports, net profit data for three consecutive years, 2022 to 2024. The research population is manufacturing companies on the IDX. This study uses purposive sampling as its methodological framework. The research sample meets the criteria set by the researcher. Determining the criteria is very important to prevent errors in selecting research samples, which can ultimately affect the results of the study. The research sample consists of 16 manufacturing companies listed on the IDX. The research findings show that partial cash flow does not affect stock prices. Accounting profit affects stock prices. Cash flow and Accounting profit simultaneously affect stock prices empirical studies conducted on invoicing companies on the Indonesia Stock Exchange.